2021
DOI: 10.1038/s41598-021-83226-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COPD on COVID-19 prognosis: A nationwide population-based study in South Korea

Abstract: Underlying chronic respiratory disease may be associated with the severity of coronavirus disease 2019 (COVID-19). This study investigated the impact of chronic obstructive pulmonary disease (COPD) on the risk for respiratory failure and mortality in COVID-19 patients. A nationwide retrospective cohort study was conducted in 4610 patients (≥ 40 years old) infected with COVID-19 between January 20 and May 27, 2020, using data from the Ministry of Health and Welfare and Health Insurance Review and Assessment Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 42 publications
8
66
0
7
Order By: Relevance
“…In a South Korea population-based retrospective cohort study of 122,040 COVID-19 cases, only 3.6% had COPD, whereas the prevailing comorbidities were asthma, hypertension, and malignancy at 27%, 26%, and 18%, respectively [22] . This result is consistent with another South Korea cohort study of 4,610 COVID-19 patients, which reported a 3.1% prevalence of COPD [23] . In another retrospective study in Mexico involving 38,342 COVID-19 patients, 29% had hypertension, 28% had obesity, 25% had diabetes, but only 3.1% had COPD [24] .…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a South Korea population-based retrospective cohort study of 122,040 COVID-19 cases, only 3.6% had COPD, whereas the prevailing comorbidities were asthma, hypertension, and malignancy at 27%, 26%, and 18%, respectively [22] . This result is consistent with another South Korea cohort study of 4,610 COVID-19 patients, which reported a 3.1% prevalence of COPD [23] . In another retrospective study in Mexico involving 38,342 COVID-19 patients, 29% had hypertension, 28% had obesity, 25% had diabetes, but only 3.1% had COPD [24] .…”
Section: Introductionsupporting
confidence: 92%
“…In a prospective cohort study of 3995 COVID-19 patients in Kuwait, 19% had hypertension, 18% had diabetes, and only 0.4% had COPD [27] . These cohort studies, however, did find that COPD patients had a worse prognosis for severe and fatal COVID-19 [22] , [23] , [24] , [25] , [26] , [27] . For reference, the COPD prevalence in the adult general population is 13-15% in South Korea [28] , [29] , 8% in Mexico [30] , 10% in Spain [31] , 5% in Iran [32] , and 7% in Kuwait [33] .…”
Section: Introductionmentioning
confidence: 91%
“…A meta-analysis by Cai et al (2021) agrees with the finding that death risk is higher for COVID-19 patients with chronic kidney failure. Likewise, a study in South Korea (Lee et al , 2021) agrees with the finding that chronic obstructive pulmonary disease is an independent cause of death among COVID-19 patients. However, a press release by the Johns Hopkins School of Public Health (2021) regarding American immunosuppressed patients, is opposite to this study´s finding that immunosuppressed COVID-19 patients have a higher death risk.…”
Section: The Effect Of Previous Health Conditionssupporting
confidence: 80%
“…As expected, COPD was associated with impaired pulmonary function in this cohort. While these patients have preexisting reduced pulmonary function due to COPD, it is also a known risk factor for all-cause mortality and progression to severe disease in COVID-19 patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%